Annotated checklist of orchids found in Merapoh Trail (Gunung Tahan, Malaysia) - Md Isa, Siti Fatimah; Mohd Salim @ Halim, Jamilah; Yong, Christina Seok Yien; Abdullah, Janna Ong; Go, Rusea (Universiti Putra Malaysia Press, 2018)
Gunung Tahan is the highest mountain peak in Peninsular Malaysia (2187 m a.s.l.) and is a part of Taman Negara Pahang that houses many rare and endemic species of flora and fauna. This account is conducted to evaluate, compile, and update the orchids collections from Gunung Tahan after almost 126 years, since the first botanical exploration was conducted by H.N. Ridley and other foreign botanist. The compilation presented in this study resulted in 294 species obtained from the selected herbarium, published record, and current expedition. A total of 57 species were recorded for recent work, out of which 18 species were new discoveries for Merapoh Trail and thus reported as new records for Gunung Tahan. IUCN Red List of Threatened Species version 2017.3 listed two species; Claderia viridiflora Hook.f. and Spiranthes sinensis (Pers.) Ames as least concern species and Paphiopedilum bullenianum (Rchb.f.) Pfitzer as endangered species. The list of the compiled species from herbarium and published records for Gunung Tahan is also included.